The roles of the personal representative In estate administration in Malaysia - Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini; Abdul Hak, Nora; Md Said, Muhamad Helmi; Miskam, Surianom (Future Academy, 2019)
The administration of an estate refers to a process of managing and distributing the deceased’s estate to the beneficiaries which take effect after his death. The tasks to administer the estate are handled by the personal representative from the beginning until the end of the administration. Appointment of a capable personal representative is therefore important as the administration of estate deals with various responsibilities throughout the entire process. This article heeds the notion that the appointment of an incompetent personal representative disrupts the process in the administration of estate that leads to adverse implications, including the misappropriation and delay in distribution of assets. This paper discusses the roles and duties of the personal representative and the comparison between the individual and institution assigned as the personal representative. This paper also highlights the challenges encountered by the personal representative in managing the estate of the deceased. As part of its research method, this qualitative legal study undertakes a library based study through the analysis of selected materials including journal articles, textbooks, statutes and cases. The findings indicate that ignorance of the roles and lack of deliberation in appointing a capable personal representative serve as factors leading to adverse management which often results in incompletion of the administration. The insights from this paper can contribute in instilling the awareness among the public as to the importance of appointing a capable personal representative in estate administration. © 2019 Published by Future Academy www.FutureAcademy.org.UK